ACO–IBR: a modified intersection‐based routing approach for the VANET. Issue 6 (3rd November 2020) - Yelure, Bhushan; Sonavane, Shefali
Abstract : The usage of dedicated short‐range communication, vehicular ad hoc network (VANET) significantly increases the security of stakeholders and improves the efficacy of the intelligent transportation system. It supports multifarious applications to make transportation convenient through routing of the messages. Changing the topological scenario, high acceleration of vehicles and intermittent communication result in the reduction of successful packet transmission and overhead. To overcome such constraints, a new routing protocol for the city environment named ant colony optimisation and intersection‐based routing (ACO–IBR) is proposed. The key objective is to identify the necessity of intersection oriented routing and selection of the route as a task of optimisation. It uses a new metric called intersection rating and a greedy approach to forward a packet through the intersection to minimise the time required to discover the route. The efforts have been made to calculate intersection rating using three parameters such as the distance between vehicles, travel direction and the time taken to reach the intersection. The performance of ACO–IBR is determined by overhead, packet delivery ratio, delay and throughput. The results are compared with the standard protocols such as greedy perimeter stateless routing, intersection‐based routing, AntHocNet and zone routing protocol. On the basis of extensive simulation, experimental results show that the ACO–IBR minimises routing overhead and improves the packet delivery ratio.